Does the "Negro" Still Need Separate Schools? Single-Sex Educational Settings as Critical Race Counterspaces. (September 2014) - Terry, Clarence L.; Flennaugh, Terry K.; Blackmon, Samarah M.; Howard, Tyrone C.
This article explores whether contemporary educators should consider single-sex educational settings as viable interventions in educating African American males. Using qualitative data from a 2-year study of single-sex educational spaces in two Los Angeles County high schools, the authors argue that when all-male spaces effectively function as Critical Race Theory counterspaces, the educational experiences of high school–aged Black males are positively transformed. These cocurricular, single-sex counterspaces can effectively shield Black males from the marginalizing effects of urban schooling while serving as platforms for productive reengagement in positive school trajectories. Research-based principles for designing effective single-sex educational settings are discussed.